STRATEGIES DE DEVELOPPEMENT RURAL EN REPUBLIQUE DEMOCRATIAUE DU CONGO - Mbombo, ISSOMALAMBE; LONGONGO, Gabriel BOSANDJA; Bolimbo, Bernard LISENDJA (IJRDO - Journal of Social Science and Humanities Research, 2021)
Within the various modalities of rural development, the DRC has resorted to various strategies for its rural development. The peasants more and more concerned to see their living conditions changed see in them the means to live these better lives.The DC to allow the change of lifestyle of its rural population, will set up multiple development strategies which unfortunately are not followed by political wills if not only intentions.The final objective pursued being to assess the state in which the rural environment of the DRC is located, to verify the different implications of these strategies through these added values.